'The new oratory': Public speaking practice in the digital, neoliberal age. (October 2020) - Rossette-Crake, Fiona
This study discusses the paradigm shift that has occurred in public speaking practice in the first two decades of the 21st century, conceptualised under the term 'the New Oratory'. The New Oratory is a product of the digital revolution in that it brings together formats that are typically relayed via videos uploaded to the Internet, and serves as a vector of the new, digital economy. Drawing on previous critical work linking language and discourse to what is referred to as the new economy, late or new capitalism or neoliberalism, the study focuses on two aspects of discourse practice that can be explained due to developments within the current economic climate: (1) the entrepreneurial speaker ethos that is embodied by the start-up generation of entrepreneurs, finds a resonance in Anglo communication culture and is closely linked to the neoliberal emphasis on branding; (2) the model of horizontal knowledge or information-sharing (in which the Internet has played a major role), whereby a move from specialist to non-specialist target audiences is shifting the frontiers of discourse communities and leading to their reorganisation. These two phenomena are illustrated via examples taken from two formats: the investor pitch and the three-minute-thesis presentation. The first belongs to the corporate sector, the second to academia. The study highlights the neoliberal forces at work outside the corporate sector per se which have come to influence most spheres of professional, social and personal lives, as well as the way these forces are ultimately being promoted by the emergence of a new, fairly homogeneous discursive setup.